Autoimmune and Paraneoplastic Chorea: A Review of the Literature - Kyle, Kevin; Bordelon, Yvette; Venna, Nagagopal; Linnoila, Jenny (Frontiers in Neurology, 2022)
Autoimmune chorea syndromes represent a vast array of paraneoplastic, parainfectious and idiopathic disorders. It is increasingly apparent that familiarity with these disorders is critically important, as they may be treatable or may be part of a syndrome requiring further work-up and monitoring. These disorders are mediated by an aberrant immunologic attack with resultant neuronal dysfunction, manifesting as chorea. These conditions are typically accompanied by other neurologic or systemic manifestations. In this review we outline the clinical features, epidemiologic factors, and delineate the specific antibodies associated with each of these autoimmune mediated disorders. We highlight up to date information regarding this heterogeneous group of disorders, including a discussion of parainfectious Sydenham's chorea; paraneoplastic syndromes associated with CRMP-5 (collapsin response mediated protein-5/CV2) and ANNA-1 (antineuronal nuclear antibody / Hu) antibodies, in addition to neuronal antibody-associated disorders including anti-NMDAR, LGI1 (leucine-rich glioma inactivated-1) and CASPR2 (contactin associated protein-2). We discuss the more recently described entities of IgLON5, which has evidence of both immunologic and degenerative pathophysiology, in addition to PDE-10A antibody-associated chorea. We also outline chorea secondary to systemic diseases including Systemic Lupus Erythematosus (SLE) and Primary Antiphospholipid Syndrome (PAPS). We provide a framework for diagnosis and treatment.